Decentralization, Systematization and Coordination in the Legislation Process in China: How does a Project Become a Law? (Sinología hispánica. China Studies Review, 2018)
This paper examines the allocation of the legislative authority of the People’s Republic of China between the central and local bodies. Given that the special administrative region system is the most characteristic, both in China and globally, a part is retained for the legislation of Hong Kong and Macao. Next, the paper analyzes the hierarchy of legal norms and the method to resolve conflicts between legal norms. Finally, the registration system is discussed to avoid contravention between the lower level law and the higher level, also, the possibility of cancellation is mentioned.